2017
DOI: 10.1186/s13014-017-0783-2
|View full text |Cite
|
Sign up to set email alerts
|

Using field size factors to characterize the in-air fluence of a proton machine with a range shifter

Abstract: Introduction: The range shifter (RS) is used to treat shallow tumors for a proton pencil beam scanning system (PBS). Adding RS certainly complicates the commissioning of the treatment planning system (TPS) because the spot sizes are significantly enlarged with RS. In this work, we present an efficient method to configure a commercial TPS for a PBS system with a fixed RS. Methods: By combining a spiral delivery with customized control points, we were able to significantly improve measurement efficiency and obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…As mentioned above, previous investigators have shown that a double Gaussian can be used to model the nuclear halo effect both in air and in medium . Shen et al and Lin et al both showed that inclusion of a double Gaussian spot profile can more accurately model FSF even for Monte Carlo dose calculation . Based on the results presented in this work, in addition to the work done by Shen et al, inclusion of this double Gaussian in the commercial TPS could help mitigate the presented disagreements.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…As mentioned above, previous investigators have shown that a double Gaussian can be used to model the nuclear halo effect both in air and in medium . Shen et al and Lin et al both showed that inclusion of a double Gaussian spot profile can more accurately model FSF even for Monte Carlo dose calculation . Based on the results presented in this work, in addition to the work done by Shen et al, inclusion of this double Gaussian in the commercial TPS could help mitigate the presented disagreements.…”
Section: Discussionsupporting
confidence: 50%
“…Additionally, many shallow treatment fields are treated with range shifters, which are expected to exacerbate the halo effect. Future investigations could include measurement of FSFs with range shifters in order to more accurately quantify these discrepancies over independent dose calculations outside of TPS …”
Section: Discussionmentioning
confidence: 99%
“…Shen8 has proposed an efficient and accurate method of using multiple FSF measurements to characterize the proton profile with fixed range shifter and therefore configure the TPS. We believe that with a well validated Monte Carlo platform, use of Monte Carlo calculated dose profile can provide an alternative and efficient method for TPS/range shifter commissioning.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the spot broadening, the air gap between the range shifter and patient should be as small as possible, though the potential for collision with the patient often requires a gap that is larger than physically optimal. Due to the generation of secondary products as well as the particle transport within the air gap, it is difficult to model the dose calculation with a range shifter analytically given a limited measured data set,5 thus an approach such as MC is desirable; the broader MC generated dataset is valuable for analytically approximating the low‐dose halo5 using multi‐Gaussian lookup tables in water or in air after a range shifter given the magnification of potential MCS and halo calculation inaccuracies by various range shifter thicknesses and air gaps 7, 8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation